Adoption of picture-based crop monitoring by agri-finance and crop advisory organizations in three Indian states is changing discourse for crop insurance among key stakeholders (government, insurers and farmers) leading to improved attitudes, behavior and relationships. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The picture-based insurance (PBI) model and related technology adopted by agri-finance and crop advisory organizations in three states (Haryana, Odisha, and Tamil Nadu) are gaining acceptance among smallholder farmers in India. Periodic stakeholder engagement led to demand-driven research on PBI, which improved knowledge/perception of crop insurance among farmers, insurers, and state governments. Image-based crop-loss and claims data from PBI brought credibility to crop insurance processes, improving farmers’ attitudes toward crop insurance, thus building trust between farmers and insurers.